Analysis of Local Culture in Improving Entrepreneurial Ability Mediated by Community Empowerment for Indigenous Papuan MSMEs in Jayapura City - Westim Ratang; Yohanis Rante; Deni Lizawani Situmorang (Transpublika Publisher, 2025)
The purpose of the research is to know and analyze the role of Department Industry, Trade and Cooperatives in empowering MSMEs for Indigenous Papuans (OAP), to know and analyze empowerment public have an impact on Papuan Indigenous People (OAP) entrepreneurship, and to know and analyze local culture influential towards Papuan Indigenous Entrepreneurship in Jayapura City. The analytical tools used on SEM with Smartpls. Empowerment of the Papuan Indigenous Micro-Business Community has been carried out by the Jayapura City Industry, Trade, Cooperatives and MSMEs Service. Empowerment is carried out by encouraging and raising public awareness of the importance of developing potentials, taking real actions such as: Education, Training, Health Improvement, Capital Provision, Information, Employment, markets and other facilities assistance. Things that have not been done by the Jayapura City Industry, Trade, Cooperatives and MSMEs Service in empowering the Community, especially Papuan Indigenous Micro-entrepreneurs (OAP) are Steps to prevent Unbalanced Competition, and protect the weak. The results of statistical tests show that local culture directly influences empowerment public for indigenous Papuan MSMEs, local culture influences the entrepreneurial ability of indigenous Papuan MSMEs and the indirect influence is that local culture influences the entrepreneurial ability of indigenous Papuan MSMEs which is supported by community empowerment.